A simple correlation for predicting the material parameter in micropolar modeling of EHD-enhanced forced convection through a flat channel - Moayedi, Hesam; Amanifard, Nima; Deylami, Hamed Mohaddes (Journal of electrostatics, 2020)
Numerical modeling of Electrohydrodynamic (EHD) induced flow in hydraulically laminar regimes has always been a discussible subject. Recently, the micropolar approach has been examined as an alternative for the aforementioned cases. The model was found to be reliable, but time-consuming, since it needed difficult attempts to make guesses at the material parameter (κω/μ). This study aims to complement and facilitate the use of this model by providing a fast tool to guess the material parameter. In this regard, the studies show that the EHD number is a sufficient criterion to predict an adequate parameter. To satisfy this purpose, a series of well-designed studies have been carried out to calculate the EHD number for different flow characteristics; Reynolds number, applied voltage, type of the collector electrode, size of the collector plate, and the arrangement of emitter electrodes. In each case, the desired material parameter has been numerically determined by trial and error. A two-dimensional flat channel was chosen as the computational model and the results of the computational attempts, which were made using the k-ε turbulence model, were selected as the basis of the appropriate material parameter estimation. •The micropolar model with an adequate material parameter can be used to model the EHD flow.•The material parameter only depends on EHD strength (NEHD).•By increasing the applied electrical voltage and decreasing the Reynolds number, NEHD and the adequate κω/μ are increased.•A general correlation for the adequate material parameter is derived based on the NEHD.